До проблеми літописного Білобережжя XIV ст. - Козубовський, Г.А. (Археологія і давня історія України, 2022)
У статті розглянуто дискусійну проблему локалізації Білобережжя XIV cт. Звертається увага
на тюркську назву ріки Південний Буг — Аксу (Біла
Вода). Її береги були місцями традиційних літніх
і зимових кочовищ і найважливіших транзитних
шляхів. Похід Ольгерда на початку 1360-х рр. було
здійснено до золотоординських центрів у басейні річок Синя Вода (Гексу) і Біла Вода (Аксу). Розкопки
пам’яток золотоординського часу в басейні р. Південний Буг можуть суттєво допомогти у вирішенні низки дискусійних питань історичної географії цього регіону. In the paper the attempt to identify the geographical
toponyms and hydronyms of the 14th century is
made. It contains an analysis of the hypotheses about
the Beloberezhye site of the 14th century in the written
sources. Based on the examination of the written, cartographic,
archeological and numismatics sources the
conception about connection of Beloberezhye with the
bank of Southern Bug River is considered.
Also, the information about origin of the river name
since antiquity till nowadays — Bug (Boh, Bug, Boug,
Bohus, Bohem and other), Hypanis, Kouβoũ (Kuvu),
Vagosola, Bagossla, Aksu (White Waters) — is discussed.
The conception, according to which the Turkik
geographical names of the river (Ak Su — White Water)
and its banks (Belobereshye — White Banks) were
the territory of the traditional summer and winter
nomads roamings has been substantiated. Also, the
certain aspects of activity of the Tartars emirs Kutlu-
Buha, Khadjibej, and Dmytro, and the landscapes of
these regions are examined. Important stimulus for development
of the trade routes in these regions were the
saline in the lower reaches of the Southern Bug and
in Black Sea region. Based on the analysis of numismatics
sources the author concludes that in the first
part — mid-14th century the trade route in Southern
Bug basin was one of the main transit trade routes in
the West territory of Golden Horde. The finds of the
silver and copper coins of the mid-14th century marked
the most important centers in the Bug River region.
After the victories of Lithuanian Prince Olgerdas over
the Hordes in 1362 at the Syny Vody (Gek-su) and
Bili Vody (Ak-su) Rivers the economic resources of the
Western Hordes were considerably reduced. According
to archaeological and numismatic data, Torhovytsia
on the Siniukha River was an important center in the
mid-14th century but was destroyed in the beginning of
the 1360s.
The issues of historical geography, many of which
can be solved by assistance of systematic archaeology
research of the Golden Horde centers in the Southern
Bug River basins are discussed in the paper.